The COVID-19 Pandemic and Enzyme Replacement Therapy in Lysosomal Storage Disorders - Asburçe Olgaç; Çiğdem Seher Kasapkara; Burak Açıkel; Yılmaz Yıldız; Gülhan Karakaya Molla; Mustafa Kılıç (Galenos Yayinevi, 2021)
Aim:The coronavirus disease-2019 (COVID-19) pandemic has caused a worldwide public health emergency, especially affecting people with chronic illnesses including lysosomal storage disorders (LSDs). The unfavorable conditions due to COVID-19 have mostly affected people with chronic conditions, in terms of disease vulnerability and access to health-care. In the present study, we aimed to assess the problems the patients with LSDs on enzyme replacement therapy (ERT) have encountered during the pandemic, and their level of anxiety. Parental evaluation has also been made for pediatric patients.Materials and Methods:A total of 19 participants were recruited. A semi-structured interview was structured to evaluate the effects of the COVID-19 pandemic on ERT. The Turkish version of "Hospital Anxiety and Depression scale" (HADS) for adult patients and parents were used to evaluate anxiety. Patients between ages 8-17 completed the child version of the Revised Child Anxiety and Depression scale (RCADS).Results:The study was completed by 19 patients, and 13 parents. Five patients (26%) admitted temporary disruption of treatment, of which the most common reason was the fear of getting infected. Eighty-nine percent of all participants were willing to receive treatment at home. Only one adult patient revealed to feel anxiety (16%). While among parents evaluated with HADS, 7/13 had scores that indicated depression and anxiety, 3/4 pediatric patients had RCADS scores indicative of anxiety and depression.Conclusion:The problems LSD patients have been facing during the pandemic, should be identified along with their attitudes regarding ERT in order to maintain the sustainability of their treatment. The psychological health of these patients should also be identified and supported, to provide optimal care to patients.